NMR spectra of oilseed rape (Brassica napus) root exudates - Alexandersson, Elin; Eriksson Röhnisch, Hanna (Swedish University of Agricultural Sciences, 2024)
The dataset contains 1D and 2D NMR spectra of root exudates from various varieties of oilseed rape (Brassica napus). A Bruker Avance III 600 MHz spectrometer connected to Topspin version 3.5 was used to record the spectra.

Included are 1D-1H-NOESY, (1H,1H)-TOCSY, (1H,13C)-HSQC, CPMG, and 1D-diffusion spectra of intact root exudates as well as 1D-1H spectra of a sample treated with ultrafiltration and solid phase extraction (SPE), respectively. The dataset further includes spectra from a spike-in experiment where different concentrations of five metabolites were added to a pooled root exudate sample as well as a blank sample. All samples have been freeze-dried and dissolved in D2O.

The data was used to develop an automated targeted metabolomics workflow called extended AQuA.

Datasetet innehåller 1D- och 2D-NMR-spektra av rotexudat från olika sorters raps (Brassica napus). Spektrumen erhölls med en Bruker Avance III 600 MHz NMR-spektrometer via Topspin version 3.5.

För intakta rotexudat finns 1D-1H-NOESY, (1H,1H)-TOCSY, (1H,13C)-HSQC, CPMG- och 1D-diffusionsspektra. I datasetet ingår även 1D-1H-spektra av ett prov som har ultrafiltrerats respektive passerat en SPE-kolonn (fastfasextraktion), samt spektra från ett spikningsexperiment där olika koncentrationer av fem metaboliter satts till både ett poolat rotexudatprov och ett blankprov. Alla prover har frystorkats och sedan lösts upp i D2O.

Datan användes för att utveckla "extended AQuA", ett automatiserat arbetsflöde för kvantitativ metabolomik.
NMR-spektra av rotexudat från raps (Brassica napus)
Keywords: rapeseed; raps; metabolic products; metaboliter; NMR spectroscopy; NMR-spektroskopi; metabolites; Brassica napus; Analytical Chemistry; Analytisk kemi; Organic Chemistry; Organisk kemi